KOLABORASI GURU BIMBINGAN DAN KONSELING DAN AGEN PERUBAHAN (ANTI PERUNDUNGAN) DALAM MELAWAN PERUNDUNGAN DI SMK NEGERI 2 BANJARBARU - Afrilia Gusman; Ani Wardah; Muhammad Eka Prasetia (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The anti-bullying and school-based violence program is an effort to prevent and deal with violence against children. This study uses a qualitative method with a phenomenological approach. The purpose of this research is to describe the vision, mission and work programs of change agents, the impact of the existence of change agents, and how collaboration between Guidance and Counseling Teachers and Change Agents. The research subjects consisted of Guidance and Counseling Teachers, members of Change Agents and Students. Data collection techniques used are observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation, drawing conclusions and verification. The results of the study are (1) Vision and Mission of the program for preventing and overcoming acts of bullying within the education unit, as an effort to prevent and deal with violence against children. Aims to create a safe and comfortable climate for students to learn. (2) The impact of the existence of a change agent for SMK Negeri 2 Banjarbaru, namely the existence of an anti-bullying change agent has a positive impact on school residents, including self-awareness to always behave well and spread kindness to fellow human beings. (3) Guidance and Counseling Teachers and Change Agents collaborate well where the Guidance and Counseling Teachers become facilitators or coaches. Meanwhile, change agents are tasked with giving or influencing friends with positive behavior and always maintaining the comfort of the school.